The Impact of Artificial Intelligenceon Taxpayer Compliance - Suryadi, Ibnu; Purba, Rebeka Meidiana; Tampubolon, Amy Septrina; Ersanti, Ersanti; Ramadhon, Rosiana (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The rapid evolution of digital technology has ushered in a new era of tax administration, characterized by the integration of Artificial Intelligence (AI). This research investigates the impact of AI implementation on taxpayer compliance, examining both the technical efficiency of tax authorities and the behavioral shifts among taxpayers. Using a comprehensive literature review and a conceptual framework based on the Technology Acceptance Model (TAM) and Deterrence Theory, this study analyzes how AI-driven tools—such as automated auditing, predictive analytics for fraud detection, and AI-powered chatbots—influence voluntary and enforced compliance. The findings suggest that AI significantly enhances compliance by reducing the "tax gap" through precise monitoring and by lowering compliance costs for taxpayers through simplified procedures. However, the study also highlights critical challenges, including data privacy concerns, the "black box" nature of AI algorithms, and the potential for digital inequality. This paper concludes that while AI serves as a powerful catalyst for transparency and efficiency, its success depends on the establishment of robust legal frameworks and ethical guidelines to maintain public trust. Keywords: Artificial Intelligence, Tax Compliance, Tax Administration, Predictive Analytics, Digital Transformation.